An assessment of the one truck lane policy along C-5 from the perspective of road maintenance and traffic management - Diaz, Miguel Eduardo V.; Intal, Prince Charlie P.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Implemented by the MMDA back in 2014, the One Truck Lane Policy is the policy that aimed to address the increasing traffic congestion along C-5 caused by the multitude of trucks traversing the road. Its main purpose was to increase the serviceability on non-truck lanes by segregating trucks into one lane - a premise that led to another problem: Road Maintenance along the truck lane meant more frequent road repairs and, therefore, higher budget allocation. This study aimed to evaluate the policy from the perspective of Traffic Management and Road Maintenance. By using Level of Service comparison, the researchers were able found that 17 of the 17 sections along C-5 demonstrated an increase in LOS. However, sudden concentrations of heavy load application on the truck lane resulted to higher rating on road conditions severity with evidences of surface distresses. This was clearly observed on sections adjacent to two intersections with short distances, as in the case of slabs of truck lane after C-5-Eastwood Avenue Intersection. With this in mind, road maintenance efforts carried out by Department of Public Works and Highways (DPWH) was evaluated specifically on their latest pavement design released by the NCR office. Due to several assumptions observed on their input parameters, following AASHTO Guide for Design of Pavement Structures, additional tests and surveys were suggested in order to correspond the actual condition of the truck lane and arrive to the most economical design of the road structure.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Truck lanes -- Manila, Philippines; Roads -- Maintenance and repair